Integer and constraint programming model formulations for flight-gate assignment problem - Ornek, M. Arslan; Ozturk, Cemalettin; Sugut, Ipek (Operational research, 2022)
Flight-gate assignment problems are complex real world problems involving different constraints. Some of these constraints include plane-gate eligibility, assigning planes of the same airline and planes getting service from the same ground handling companies to adjacent gates, buffers for changes in flight schedules, night stand flights, priority of some gates over others, and so on. In literature there are numerous models to solve this highly complicated problem and tackle its complexity. In this study, first, we propose two different integer programming models, namely, timetabling and assignment based models, and then a scheduling based constraint programming model to solve the problem to optimality. These models prove to be highly efficient in that the computational times are quite short. We also present the results for one day operation of an airport using real data. Finally, we present our conclusions based on our study along with the possible further research.